FEEDING PATTERN WITH NUTRITIONAL STATUS IN CHILDREN AGED 11-12 YEARS AT SD 04 SEPANJANG JAYA BEKASI CITY IN 2023 - Leonardo, Marco; Suryani, Rotua; Nurti Y.K. Gea (Jurnal Medicare, 2024)
Beckground : The body's physiological function needs, as well as social and emotional needs, everyone needs to eat (consume food) with the right diet. Fulfillment of the amount of food and nutrients that are good for the body will lead to a better quality of one's health and this will have a positive impact on one's education. Adequate nutrition plays an important role during school age to ensure these children achieve their full or optimal growth, development and health potential. Weight is often a problem, triggering an increase in the prevalence of obesity and the emergence of eating disorders (malnutrition). Research Objectives : Knowing the Relationship Between Feeding Patterns and Nutritional Status in Children Aged 11-12 Years at SDN 04 Sepanjang Jaya Bekasi City in 2023 Research Methods : The research method used is quantitative with cross-sectional analytic research. The population in this study were children aged 11-12 years in grades 5 and 6 at SDN 04 Sepanjang Jaya, Bekasi City, consisting of 66 people. Research results : From the results of statistical analysis, it was obtained that the value of α was 5% (0.05) the results of the Chi-Square Test obtained a p-value (0.000) < the value of α (0.05) so that it could be concluded from these results that H0 was rejected and Ha was accepted. Conclusion : There is a Relationship between Feeding Patterns and Nutritional Status in Children Aged 11-12 Years at SDN 04 Sepanjang Jaya, Bekasi City.